Cultural heritage in Brazilian legislation and areas of protection of cultural environment in Rio de Janeiro - Batista, Vanessa Oliveira; Macedo, Carmen Lúcia (Políticas Culturais em Revista, 2011)
Abstract: This paper aims to present the evolution of legislative protection of cultural heritage in Brazil. We chose to broaden the discussion, having a starting point at the definition of cultural heritage and its regulation in an international level in order to achieve the Brazilian legal system, specifically focusing on Rio de Janeiro, and contextualizing it in the contemporary world. The chapter on our legislation includes a draft of Mario de Andrade, the Decree-Law 35/1937; the Federal Constitution of 1988 and Decree 3551/2000. We make the legal treatment of the theme in Rio de Janeiro explicit; former seat of the Brazilian Empire and a former federal capital, full of monuments and areas of cultural preservation. KEYWORDS: Cultural heritage. Preservation. Rio de Janeiro. O patrimônio cultural na legislação brasileira e as áreas de proteção do ambiente cultural no Rio de Janeiro RESUMO: Este trabalho tem por objetivo apresentar a evolução legislativa da proteção ao patrimônio cultural no Brasil. Escolhemos ampliar a discussão, partindo da definição de patrimônio cultural e sua regulamentação no âmbito internacional para atingir o ordenamento jurídico brasileiro, em especial o do Rio de Janeiro, e contextualizá-lo no mundo contemporâneo. O capítulo relativo à nossa legislação abrange o anteprojeto de Mario de Andrade, o Decreto-lei 35/1937, a Constituição Federal de 1988 e o Decreto 3551/2000. Em capítulo específico explicitamos o tratamento jurídico dado ao tema na cidade do Rio de Janeiro, antiga sede do Império e ex-Capital Federal, rica em monumentos e áreas de preservação cultural. PALAVRAS CHAVE: Patrimônio cultural. Preservação. Rio de Janeiro